Penggunaan Media “Alga Maji” Untuk Meningkatkan Hasil Belajar PAI Materi Haji Dan Umrah Kelas IX A SMP Negeri 4 Gantung - Heriyanto Heriyanto (Jurnal Didaktika Pendidikan Dasar, 2020)
The aim of this learning innovation is to realize 21st century learning and the era of the industrial revolution 4.0 namely critical thinking, collaborating, communicating effectively, and creativity in learning and shaping the character of learners, as well as increasing understanding and learning outcomes in Hajj and Umrah material for class IX A SMP Negeri 4 Gantung, East Belitung Regency, Bangka Belitung Islands. Based on the results of a questionnaire from students and direct observation conducted by the teacher, as well as the results of evaluations that have been carried out, the use of the media "Alga Maji" and Hajj Videos on Hajj material in class IX A obtained results, namely learning by using the tools "Alga Maji" and The Hajj video can create 21st century learning and the 4.0 revolution era, namely critical thinking and collaboration in solving problems, in describing and explaining the order of the implementation of the pilgrimage. In addition, the use of the media "Alga Maji" and Video Hajj is also able to shape the character of the brave and confident students appear in front of the class when presenting the implementation of the pilgrimage and be responsible and trustful when getting assignments.